Alexandria and Rome: representations, dynamics and vicissitudes in the sphere of the Ptolemaic power - Clímaco, Joana Campos (Romanitas - Revista de Estudos Grecolatinos, 2017)
The Roman expansion through the Eastern Mediterranean was a complex process involving diplomacy, alliances and conflicts with ancient kingdoms established in a region of enormous cultural diversity and resulted in the gradual absorption of these territories to direct control by Rome. Ptolemaic Egypt was the last huge Hellenistic kingdom to be conquered and its process of annexation was postponed for its differentiated value to Rome in several aspects. The Greco-Roman literature point to some moments of the dynasty’s life, especially the occasions of contacts and tensions with Rome. The intention of this article is to evaluate how these sources represent the Ptolemaic succession in order to highlight the internal “chaos” of the dynasty while justifying the need for the Roman “order” in the territory.